2020
DOI: 10.1111/raq.12475
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on utilization of macrophytes as feed ingredient for fish in future aquaculture

Abstract: Aquaculture activity supplies high-quality protein at affordable cost. A global call for foods of aquatic origin has heightened not only due to the zooming population growth, but also because of a choice of healthier foods for human beings. As the industry expands, it is facing the high cost of feeding because the key ingredients, that is fishmeal and fish oil, of aquadiet are very expensive. Identification of alternate foodstuffs that will remarkably minimize the expense of productivity of animal protein beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 130 publications
(277 reference statements)
0
16
0
1
Order By: Relevance
“…Aquaculture contributes high-quality protein at a relatively reasonable cost, providing nearly 16% of the world's human-acquired protein (Naseem et al, 2021). Protein is also one of the main nutrients for aquatic animals, and the quality and quantity of protein directly determine the cost of feed.…”
Section: Introductionmentioning
confidence: 99%
“…Aquaculture contributes high-quality protein at a relatively reasonable cost, providing nearly 16% of the world's human-acquired protein (Naseem et al, 2021). Protein is also one of the main nutrients for aquatic animals, and the quality and quantity of protein directly determine the cost of feed.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that the yield of crayfish under feeding conditions (SF and NF) was significantly higher than that under no feeding conditions (SN and NN). As the direct food source for crayfish, feed can effectively promote their growth (Mukherjee et al, 2010;Naseem et al, 2020). Interestingly, our research found that the yield of crayfish in the SF condition was 13% higher than that in the NF condition, and the value in the SN condition was 2.3% higher than that in the NN condition (Table 4).…”
Section: Discussionmentioning
confidence: 72%
“…Aquaculture provides protein for human nutrition (Nissa et al, 2021), but the eutrophication and environmental pollution caused by intensive aquaculture production are widespread (Herbeck et al, 2013;Bian et al, 2012). The eutrophication of water bodies during intensive aquaculture is mainly caused by the nitrogen and phosphorus from unconsumed feed (Cantas and Yildirim., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic disorders can occur in fish when dietary protein requirements are not met (Zhang et al, 2016). Even though many studies report various protein levels for rainbow trout, a minimum of 40% crude protein is considered to be necessary for its diet, in general terms (NRC, 1993). In our study, we prepared four isonitrogenous diets to contain 43.25 ± 0.26 (mean ± SE) crude protein per 100 g of the diet, which is in line with NRC (1993) and with newer studies conducted on rainbow trout broodstock (Ma et al, 2019; Vassallo‐Agius et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, amino acid analyses were performed on experimental diets, whether the required essential amino acid levels are met. Based on findings, all essential amino acids were above the requirements of rainbow trout (NRC, 1993).…”
Section: Discussionmentioning
confidence: 99%